2000
DOI: 10.1148/radiographics.20.4.g00jl081073
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cardiac and Pericardial Neoplasms: Radiologic-Pathologic Correlation

Abstract: Primary cardiac and pericardial neoplasms are rare lesions and include both benign and malignant histologic types. Myxoma is the most frequent primary cardiac neoplasm, but other benign tumors include papillary fibroelastoma, rhabdomyoma, fibroma, hemangioma, lipoma, and paraganglioma. Cardiac sarcoma represents the second most common primary cardiac neoplasm. Lymphoma can also affect the heart primarily. Pericardial tumors that affect the heart include benign teratomas and malignant mesotheliomas. Patients af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
450
1
41

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(496 citation statements)
references
References 105 publications
4
450
1
41
Order By: Relevance
“…Cardiac hemangiomas have a non-specific pattern on unenhanced CT but in most cases, they show intense enhancement with contrast [6] . Cardiac MRI provides a more specific image and may provide a qualitative diagnosis [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac hemangiomas have a non-specific pattern on unenhanced CT but in most cases, they show intense enhancement with contrast [6] . Cardiac MRI provides a more specific image and may provide a qualitative diagnosis [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Myxomas can be spherical or ovoid shaped; have smooth margins; consist of various components, such as myxoid and fibrous tissue and calcifications; and can exhibit hemorrhaging. Myxomas display low to iso-density on non-contrast-enhanced CT (14,18). Calcification is more common in right atrial masses and is clearly shown on CT. On MRI, myxomas typically display low intensity on T1WI and high intensity on T2WI; however, they sometimes exhibit heterogeneous signal intensity due to mucoid degeneration or hemorrhaging (21).…”
Section: Myxomamentioning
confidence: 99%
“…1)2) Because of their rarity, it is very difficult to generalize about the initial clinical presentation and the clinical courses of the specific neoplasms. These tumors demonstrate aggressive behavior and extremely poor prognosis.…”
Section: In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
“…Primary cardiac tumors are rare, with an incidence of 0.02%. 1) Majority of these tumors are benign, with myxoma comprising 50% of primary cardiac tumors. Malignant tumors account for 25% of primary cardiac tumors.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%